2004
DOI: 10.1182/blood-2003-11-3943
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor CCR7 induces intracellular signaling that inhibits apoptosis of mature dendritic cells

Abstract: Acquisition of CCR7 expression is an important phenotype change during dendritic cell (DC) maturation that endows these cells with the capability to migrate to lymph nodes. We have analyzed the possible role of CCR7 on the regulation of the survival of DCs. Stimulation with CCR7 ligands CCL19 and CCL21 inhibits apoptotic hallmarks of serum-deprived DCs, including membrane phosphatidylserine exposure, loss of mitochondria membrane potential, increased membrane blebs, and nuclear changes. Both chemokines induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(170 citation statements)
references
References 46 publications
8
160
1
1
Order By: Relevance
“…In addition, it was shown that elevations of intracellular calcium are not necessary for directional migration of mouse neutrophils [36]. However, a recent publication, dealing with the dissection of chemokine receptor transduced signaling pathways, showed clearly that, in human monocyte-derived DC, chemokineinduced migration through CCR7 depended on the MAPK pathways, especially on ERK1/2 activity, whereas signaling through the PI3Kc/PKB pathway was responsible for mediating anti-apoptotic effects but not chemotaxis [34,51,52]. Apart from that, by comparing the impact between CCR7 and CXCR4 engagement on mature DC, we found a close association between ERK activity, especially ERK-1 activity, and the outcome of a chemotactic response in human monocyte-derived DC [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that elevations of intracellular calcium are not necessary for directional migration of mouse neutrophils [36]. However, a recent publication, dealing with the dissection of chemokine receptor transduced signaling pathways, showed clearly that, in human monocyte-derived DC, chemokineinduced migration through CCR7 depended on the MAPK pathways, especially on ERK1/2 activity, whereas signaling through the PI3Kc/PKB pathway was responsible for mediating anti-apoptotic effects but not chemotaxis [34,51,52]. Apart from that, by comparing the impact between CCR7 and CXCR4 engagement on mature DC, we found a close association between ERK activity, especially ERK-1 activity, and the outcome of a chemotactic response in human monocyte-derived DC [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, metastatic SCCHN cells have been shown to express chemokine receptor 7 (CCR7), which may enable their access to the lymphatic system and facilitate spread to regional lymph nodes (Wang et al, 2004). Immune cells utilize CCR7 to transmit a prosurvival signal, mediated by the phosphoinositide-3 kinase (PI3K)/protein kinase B (PKB/Akt) cascade (Pilkington et al, 2004;Sa´nchez-Sa´nchez et al, 2004), which may be analogous in epithelial cancer cells. In order to determine the mechanism(s) by which chemokines promote tumor growth and spread, we have studied the downstream events mediating CCR7-induced migration, invasion, and survival in metastatic SCCHN cells.…”
Section: Introductionmentioning
confidence: 99%
“…This observation may have been due, at least in part, to the effects of CCR7 on resistance to adjuvant radiation therapy. Since CCR7 signalling in normal immune cells mediates a pro-survival signal through the PKB/AKT cascade (Pilkington et al, 2004;Sanchez-Sanchez et al, 2004), it is also possible that this pathway may influence outcome in response to treatment in head and neck cancers. Therefore, patients with primary tumours that express high levels of CCR7 may be good candidates for enrolment in studies of new agents that target the CCR7-PI-3K-PKB/AKT axis.…”
Section: Discussionmentioning
confidence: 99%